Patient Preferences for Multiple Myeloma Treatments: A Multinational Qualitative Study - Janssens, Rosanne; Lang, Tamika; Vallejo, Ana; Galinsky, Jayne; Plate, Ananda; Morgan, Kate; Cabezudo, Elena; Silvennoinen, Raija; Coriu, Daniel; Badelita, Sorina; Irimia, Ruxandra; Anttonen, Minna; et al. (Frontiers in Medicine, 2021)
BACKGROUND: Investigational and marketed drugs for the treatment of multiple myeloma (MM) are associated with a range of characteristics and uncertainties regarding long term side-effects and efficacy. This raises questions about what matters most to patients living with this disease. This study aimed to understand which characteristics MM patients find most important, and hence should be included as attributes and levels in a subsequent quantitative preference survey among MM patients. METHODS: This qualitative study involved: i) a scoping literature review, ii) discussions with MM patients (n=24) in Belgium, Finland, Romania, and Spain using Nominal Group Technique, iii) a qualitative thematic analysis including multi-stakeholder discussions. RESULTS: MM patients voiced significant expectations and hopes that treatments would extend their lives and reduce their cancer signs and symptoms. Participants however raised concerns about life-threatening side-effects that could cause permanent organ damage. Bone fractures and debilitating neuropathic effects (such as chronic tingling sensations) were highlighted as major issues reducing patients' independence and mobility. Patients discussed the negative impact of the following symptoms and side-effects on their daily activities: thinking problems, increased susceptibility to infections, reduced energy, pain, emotional problems, and vision problems. MM patients were concerned with uncertainties regarding the durability of positive treatment outcomes, and the cause, severity, and duration of their symptoms and side-effects. Patients feared short-term positive treatment responses complicated by permanent, severe side-effects and symptoms. CONCLUSIONS: This study gained an in-depth understanding of the treatment and disease-related characteristics and types of attribute levels (severity, duration) that are most important to MM patients. Results from this study argue in favor of MM drug development and individual treatment decision-making that focuses not only on extending patients' lives but also on addressing those symptoms and side-effects that significantly impact MM patients' quality of life. This study underscores a need for transparent communication towards MM patients about MM treatment outcomes and uncertainties regarding their long-term efficacy and safety. Finally, this study may help drug developers and decision-makers understand which treatment outcomes and uncertainties are most important to MM patients and therefore should be incorporated in MM drug development, evaluation and clinical practice.